PELATIHAN PEMBUATAN ECO ENZYM SECARA ONLINE DARI SAMPAH BUAH DAN SAYURAN SEBAGAI DISINFECTANT DAN HAND SANITIZER HERBAL KEPADA GURU-GURU SMK PUSAT KEUNGGULAN - Lina Arliana Nur Kadim; Indah Ambarita; Yani Maulita; Novriyenni Novriyenni; Magdalena Simanjuntak; Suci Rahmadani; Ahmad Fauzi; Anton Sihombing (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Garbage is a waste material as a result of human activities which is a material that can no longer be used. Waste is solid waste consisting of organic and inorganic substances which are considered useless and must be managed so as not to harm the environment. Including organic waste, one of which is waste that comes from kitchen waste in every household, namely fruit and vegetable peel waste. Waste processing to reduce pollution and preserve the environment is to process waste into Eco Enzymes. The purpose of making Eco Enzyme is to process enzymes from organic waste that are usually thrown into trash cans into disinfectants and hand sanitizers.